The Influence of Apatheism, Agnosticism & Pluralism on the Ecclesiastical Understanding of Generation Z - Raymond Maxwell Njotorahardjo; Frederich Oscar L Lontoh; Juanda Juanda (Jurnal Didaskalia, 2023)
Generation Z constitutes 25.9% of the global population and 27.9% in Indonesia. They represent the first generation with the largest post-Christian figures, as they have departed from Christianity and the church. This is influenced by the rapid growth of apatheism, agnosticism, and pluralism in the modern era. The aim of this research is to determine whether apatheism, agnosticism and pluralism have affected the understanding of Generation Z, aged 18-26, in Java and Bali regarding local church life. This study employs a quantitative approach, utilizing questionnaires with 3,500 respondents representing the Generation Z population aged 18-26 in IFGF churches in Java and Bali. The research results indicate that there is a 41% simultaneous influence between apatheism, agnosticism, and pluralism on the understanding of church life among Generation Z. Specifically, apatheism exerts a 34.9% influence, agnosticism has a 10.2% impact, and pluralism holds a 39.5% influence on the understanding of church life among Generation Z. The conclusion drawn from these findings indicates that apatheism influences Generation Z to become indifferent to God and the church. Apatheism inhibits the beliefs of Generation Z in the absolute truth within Jesus, hindering church involvement. Pluralism leads Generation Z to stop sharing the gospel with others, citing the need to respect diverse beliefs. Therefore, the church and families need to collaborate in teaching and discipling Generation Z regarding a proper understanding of church life and the dangers of these ideologies.